PERBEDAAN HASIL BELAJAR MAHASISWA PADA MATAKULIAH MATEMATIKA ANTARA LULUSAN SEKOLAH JURUSAN IPA DAN JURUSAN IPS - AMINULLAH AMINULLAH; KUSMIANTI KUSMIANTI (GANEC SWARA, 2022)
The purpose of this study is to describe the differences in student learning outcomes in mathematics courses between school graduates majoring in science and social studies. The type of research used is non-experimental quantitative research, namely comparative research. The sample of this research is the students of UNMAS Denpasar PSDKU Mataram Campus. The results showed that (1) the average (mean) learning outcomes of students majoring in science were 71.78 while the average learning outcomes for students majoring in social studies was 62.50. This means that in terms of the average learning outcomes, it can be said that the learning outcomes of students majoring in science are higher than the learning outcomes of students graduating from social studies and the standard deviation of learning outcomes for social studies graduates is greater than that of science. (2) There is a significant difference in student mathematics learning outcomes between school graduates majoring in science and social studies with a significant number of 0.024 < 0.05 at UNMAS Denpasar PSDKU Mataram Campus